PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP AGRESIVITAS PAJAK YANG DI MODERASI DENGAN MEKANISME CORPORATE GOVERNANCE - Daisy Puspita Ningrum (2020)
This study aims to analyze the effect of corporate governance mechanisms on the relationship of corporate social responsibility disclosure to tax aggresiveness. In this study tax aggresiveness is proxied using book tax difference (BTD). This study uses 98 companies listed on the indonesia stock exchange (IDC) manufacturing sector. This study uses panel data regression analysis techniques. The results of the study are (1) CSR disclosure has no significant effect on tax aggresiveness. (2) the audit comittee does not moderate the relationship of CSR disclosure to tax aggresiveness. (3) independent commisioners do not moderate the relationship of CSR disclosure to tax aggresiveness. (4) audit quality does not moderate the relationship of CSR disclosure to tax aggresiveness.